PENGGUNAAN KALIMAT DALAM TEKS BERITA SISWA KELAS VIII B SMP PEMBANGUNAN LABORATORIUM UNP TAHUN AJARAN 2018 - Ilaturahmi, Auzi; Thamsin, Andria Catri (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACTÂ The purpose of this study was to describe the use of sentences in the news text of class VIII B SMP Pembangunan Laboratorium UNP academic year 2018. This type of research is qualitative research with descriptive methods. The research entry is the news text writing of class VIII B students, amounting to 28 texts from 28 people. Data collection is done through documentation studies. Data were analyzed by referring to the Miles and Huberman models with steps, namely (1) doing data reduction, (2), displaying data, and (3) making conclusions and verification (conclusion drawing / verification). Based on the results of the study, the use of sentences used in the text includes single sentences and compound sentences. The use of single sentences was found 105 (57%) of 183 sentences as research data. Whereas, compound sentences were found 78 (42%) of 183 sentences as research data. The use of sentences based on single sentences is found 81 (76%) verbal predicate sentences of 105 single sentences, 8 (8%) numeral predicate sentences of 105 single sentences, 7 (7%) nominal sentences of 105 single sentences, 6 (6%) sentences the sentence has an adjunctival predicate of 105 single sentences, and 3 (3%) prepositional prediction of 105 single sentences. Then, the use of sentences based on compound sentences found 41 (53%) compound sentences equivalent from 78 compound sentences and 37 (47%) multilevel compound sentences from 78 compound sentences.Â Kata kunci: Teks Berita, Penggunaan Kalimat